The Ethics of Artificial Intelligence Users in Education 5.0 - Bùi Minh Thuận (Journal of Technical Education Science, 2025)
In the era of education 5.0, artificial intelligence (AI) becomes popular and its application in education has achieved certain results. In addition, it also brings many benefits such as personalizing learning or promoting student participation in learning. In addition, many ethical challenges are raised in the use of artificial intelligence. AI users in education need to comply with ethical principles to ensure transparency, fairness and protect the privacy of learners. Unlike education 4.0, when only focusing on technology, education 5.0 has changed, focusing more on the human factor, humanity in education, ethics becomes a more essential factor than ever when taking people as the center. Therefore, it is necessary to ensure that AI is used responsibly and does not harm users and those affected. In addition, the study also mentions what a digital citizen needs to be able to adapt to education 5.0. This is also an important part in building a safe and effective learning and development environment.